Proportional Tumor Infiltration of T Cells via Circulation Duplicates the T Cell Receptor Repertoire in a Bilateral Tumor Mouse Model - Tsunoda, Mikiya; Aoki, Hiroyasu; Shimizu, Haruka; Shichino, Shigeyuki; Matsushima, Kouji; Ueha, Satoshi (Frontiers in Immunology, 2021)
Temporal analysis of the T cell receptor (TCR) repertoire has been used to monitor treatment-induced changes in antigen-specific T cells in patients with cancer. However, the lack of experimental models that allow a temporal analysis of the TCR repertoire in the same individual in a homogeneous population limits the understanding of the causal relationship between changes in TCR repertoire and antitumor responses. A bilateral tumor model, where tumor cells were inoculated bilaterally into the backs of mice, could be used for temporal analysis of the TCR repertoire. This study examined the prerequisite for this strategy: the TCR repertoire is conserved between bilateral tumors that grow symmetrically. Bilateral tumors and draining lymph nodes (dLNs) were collected 13 days after tumor inoculation to analyze the TCR repertoire of CD4+ and CD8+ T cells. The tumor-infiltrating T-cell clones were highly similar between the bilateral tumors and expanded to the similar extent. In addition, the differences of TCR repertoire between the bilateral tumors was equivalent to Intra-tumoral heterogeneity on one side. On the other hand, the similarity of the TCR repertoire in the bilateral dLNs was markedly lower than that in the tumor, suggesting that tumor-reactive T cell clones induced independently in each dLN are mixed during recirculation and then proportionally infiltrated the bilateral tumors. These findings suggest that our bilateral tumor model is suitable for monitoring of temporal and treatment-induced changes in tumor-reactive T cell clones.